Nutritional status of yellow passion fruit submitted to nitrogen sources by fertigation - Moura, Regiana dos Santos; Marques, Adenaelson de Sousa; Santos Silva, Elton Jonh; da Silva Junior, Gabriel Barbosa; de Sousa, Tiago Medeiros; da Silva, Everaldo Moreira (Comunicata Scientiae, 2018)
Yellow passion fruit is the most cultivated species in Brazil and requires high amounts of nitrogen and an adequate nutritional status to express its entire productive potential. In this sense, this study aimed to evaluate the effect of different sources and doses of nitrogen via fertigation on nutritional status and leaf chlorophyll of yellow passion fruit. The experiment was conducted from June 2013 to August 2014 in Gurgueia Valley, Cristino Castro county, Piaui State, Brazil. The experimental design was randomized blocks with four replications, in a 2 x 5 factorial design related to the application of two nitrogen sources (urea and ammonium sulfate) and five N levels (100, 200, 300, 400 and 500 kg ha-1 year-1). Six plants per replication were considered, totaling 240 plants, spaced 3 m between rows and 3 m between plants, and covering an area of 2,160 m2. At pre-flourishing, it was evaluated leaf chlorophyll index and leaf nitrogen, phosphorus, potassium, calcium, magnesium and sulfur contents. Urea increases Ca and Mg leaf contents and reduces leaf S content in relation to ammonium sulfate. The increase in nitrogen fertilizing levels enhances leaf N and Mg concentrations. For Ca, the optimal ammonium sulfate dose is 296.30 kg ha-1.